Post-partum thyroiditis can be painful. Issue 772 (February 1990) - Othman, S.; Parkes, A. B.; Richards, C. J.; Hall, R.; Lazarus, J. H.
Abstract : A patient with post-partum thyroiditis is described. She was a 22 year old with a negative family history of autoimmune thyroid disease who was noted to have a high titre of antithyroid microsomal antibody during pregnancy. She developed mild hyperthyroidism 8 weeks post-partum but at 12 weeks she had a mildly painful enlarged thyroid gland. At 20 weeks post-partum she had severe thyroidal pain with dysphagia. The thyroid was exquisitely tender to palpation. She was treated with L-thyroxine and the pain resolved within 4 weeks. This is the first report documenting pain in the thyroid as a feature of post-partum thyroiditis.